Sustainable Cities and Urban Landscape – Need of the Hour (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Landscape is more than a beautiful sight. Landscape is a term used frequently to describe theholistic view of the natural world, which is to say, the awareness of daily habitat or the outcome of theinteraction between natural forces and human activities. The purpose here is to point out how a wiseunderstanding and managing of the landscape phenomena largely contributes to a sustainable city. Aseparation between urban residents and local natural processes and expressions has resulted from aperspective on nature that reduces it to savor the goodness of immediate material resources and wastedisposal services, or to satisfy unpleasant alien aesthetics.In order to replace or make up for the lostnatural energy, society has been urged to develop new forms of energy under the pretense ofsustainability. Residents of urban settlements may perceive, experience, and breathe the progressivemodification of the landscape, and they may also value, control, and plan it, giving sustainability basedon a sense of place a concrete and practical significance. A sizable portion of professional work derivedfrom landscape knowledge and thought can make a substantial contribution to sustainability.